2013
DOI: 10.1002/j.1532-2149.2013.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental hypothyroidism during pregnancy affects nociception and locomotor performance of offspring in rats

Abstract: EGH promotes hypersensitivity to noxious thermal but not mechanical stimulus. Moreover, motor force is similarly reduced in male and female OMTDs, whereas motor performance is reduced only in mature male OMTD, suggesting the presence of a protective factor in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…The pain sensitivity has been documented to be related with thyroid status [4]. An adequate support of maternal thyroid hormones may be required to ensure a normal nociceptive function of offspring into adulthood [5]. However, information regarding the underlying mechanism of thyroid hormones in affecting pain processing and synaptic transmission in the anterior cingulate cortex (ACC), which is highly involved in the pain modulation, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The pain sensitivity has been documented to be related with thyroid status [4]. An adequate support of maternal thyroid hormones may be required to ensure a normal nociceptive function of offspring into adulthood [5]. However, information regarding the underlying mechanism of thyroid hormones in affecting pain processing and synaptic transmission in the anterior cingulate cortex (ACC), which is highly involved in the pain modulation, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient maternal thyroid hormones may be necessary to determine a normal nociceptive function of offspring. 14 Previous study showed that hypersensitivity may alter motor coordination, and avoidance behaviour. 15…”
Section: Perinatal Hypothyroidism Decreased Nociceptive Thresholdmentioning
confidence: 99%
“…In athyreotic patients, the pain sensitivity was associated with the thyroid status [61] . It has also been reported that an adequate supply of thyroid hormones from mother rats is necessary to acquire a normal nociceptive function in the offspring into adulthood [62] . Using experimental hypothyroidism mice that were treated with potassium perchlorate and methimazole in the drinking water, it was investigated whether and how synaptic transmission and pain perception in the ACC are modulated by thyroid hormones [63] .…”
Section: Hypothyroidismmentioning
confidence: 99%